4,4?-dibenzyl-5,5?-(pyridine-2,6-diyl)bis(3,4-dihydro-2H-1,2,4-triazole-3-thione) - Demir, S; Dinçer, M; Çetin, A; Dayan, O; Cansiz, A (Int Union Crystallography, 2006)
The title compound, C23H19N7S2, adopts the ketoamine tautomeric form and displays C-H center dot center dot center dot N hydrogen-bonding interactions. There are two independent molecules in the asymmetric unit.